2017
DOI: 10.1177/1538574416687733
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Embolization of Type I Endoleaks Associated With Endovascular Abdominal Aortic Aneurysm Repair Using Ethylene Vinyl Alcohol Copolymer

Abstract: Type I endoleaks can be safely and effectively treated by embolotherapy with EVOH. Larger endoleaks resulting from grossly undersized endografts appear to be unsuitable for EVOH embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The flow diagram of the systematic search and selection is presented in Figure 3 . Finally, 21 papers (12 original articles, 9 case reports) were included; examination of the references did not produce additional records [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. None of the studies was randomized and none reported complete raw data, while some articles reported a selection of single-patient data; as a result, a meta-analysis could not be performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow diagram of the systematic search and selection is presented in Figure 3 . Finally, 21 papers (12 original articles, 9 case reports) were included; examination of the references did not produce additional records [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. None of the studies was randomized and none reported complete raw data, while some articles reported a selection of single-patient data; as a result, a meta-analysis could not be performed.…”
Section: Resultsmentioning
confidence: 99%
“…Five different ELIA approaches were described, the most used was transarterial embolization accessing the femoral artery (13/21, 62%) or the brachial/radial artery (6/21, 29%), two studies report on a percutaneous transabdominal approach [ 14 , 19 ], one on a translumbar approach [ 21 ] and two case reports on a transcaval approach [ 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a total of ten eligible studies were included for analysis; review of the references yielded no additional studies. (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) No meta-analysis could be performed since none of the included studies were randomized trials nor were there control groups reported.…”
Section: Search Resultsmentioning
confidence: 99%
“…These ten studies described 194 patients who received liquid embolics as the sole treatment for T1EL after EVAR. (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), 9 (4.6%) patients received treatment for ruptured aneurysms, in six cases initial EVAR for a ruptured aneurysm was directly followed by embolization of the T1EL. (18, 22, 23) Ierardi et al described three patients treated for secondary aneurysm rupture after EVAR caused by a late T1EL, for which embolization was performed.…”
Section: Study Descriptivesmentioning
confidence: 99%
“…Moreover, in this situation there is always a certain risk of Onyx reflux. 25 Endoanchors are designed to enhance endograft proximal fixation and sealing. The ANCHOR registry compared the prophylactic use of the anchors with their use in the treatment of proximal aortic neck complications and found better technical success (absence of a type Ia endoleak at completion angiography) for the former (89.7% vs 80.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%